Financial liberalization and growth: an overview - Gündüz, Seda (My University, 2002)
Financial liberalization policies that are discussed with McKinnon and Shaw hypothesis through the first period of seventies has created important impacts from the point of not only the functioning of financial markets but also the performance of the whole economic system. The aim of this assertation is to survey the studies that focus on the relationship between financial system and economic development. Through the developments of financial intermediary theories and the endogenous growth model during the eighties, the positive impact of financial liberalization on the real economic activity has been proved theoretically and emprically. It is claimed that deep financial market which completes its development process through sophisticated financial intermediaries and liquid and large capital market is an appropriate ground for international integration process. The international integration policies that are implemented without theoretical proofs and emprical evidences make the countries' economies disturb. The assumption of the international integration will give impetus to financial development and economic growth processes is collapsed. Then, the importance on the economic conditons on the functioning of financial markets is analyzed. This perspective directs debates to the importance of the sequencing and speed problems of policies. Conclusively, it is understood clearly that, the special characteristics of the economy determine how financial markets perform and how the real economic activity is affected from this performance. The requirements of the real Per capita income that exceed a threshold level, sound domestic financial system, law of order, political stability are emphasized notably.

70' lerin ilk periodunda McKinnon ve Shaw tarafından ortaya konulan finansal liberalizasyon politika önerileri, sadece finansal piyasaların işleyişi açısından değil, reel ekonominin performansı bakımından da önemli sonuçlar yarattı. Bu çalışmanın amacı reel ekonominin kalkınma süreci ve finansal piyasaların işleyişi arasındaki ilişkiyi inceleyen çalışmaların literatür taramasını yapmaktır. Seksenler boyunca gelişen endojen aracı kurumlar ve endojen büyüme modelleri, finansal piyasalar ve reel ekonomik performans arasında varsayılan pozitif ve tek yönlü ilişkiyi hem teorik, hem de ampirik olarak ispatlamışlardır. Bunun takibinde, hem karmaşıklaşmış aracı kurumlar hem de zamanla genişleyen ve likit hale gelen sermaye piyasaları sayesinde gelişme sürecini tamamladığı varsayılan finansal piyasaların, uluslararası piyasalara açılmak için uygun bir zemin oluşturduğuna inanılmış; ulusal finansal piyasaların uluslararası piyasalara eklemlenme sürecine hız verilmiştir; fakat baş döndürücü bir hızla uygulanan politikaların reel ekonomilerde yarattığı hezimet sonucu, tekyönlü varsayılan ilişkinin diğer boyutu da ele alınmış, reel ekonominin finansal piyasaların işleyişi üzerindeki etkisi incelenmeye başlanmış ve ulusal finansal piyasalar için yapılmış varsayımların, ispatı yapılmadan uluslar arası piyasalara uygulanmasının teorik ve ampirik boşluğu ciddi eleştirilere maruz kalmıştır. Daha sonra dikkatlerini bu politikaların uygulama sırasına ve hızına çeviren iktisatçılar, her ülkenin kendi koşulları göz önünde bulundurulmadan, gözü kapalı bir şekilde bu politikalara dahil edilmesine karşı çıkmışlar ve belli bir seviyeyi aşması gereken, reel ekonomik performans, sağlıklı ulusal finansal yapı, güvenilir hukuk sistemi ve politik istikrar gibi gereklilikleri önemle vurgulamışlardır.
Keywords: Ekonomi; Finans